The single monetary policy and domestic macro-fundamentals: Evidence from Spain - Michael G. Arghyrou; Maria Dolores Gadea (Cardiff University, Cardiff Business School, 2008)
We model pre-euro Spanish monetary policy and use our findings to assess the compatibility of the interest rates set by the ECB since 1999 with Spanish macrofundamentals. We find that in the 1990s Spain implemented successfully a monetary strategy tailored to its own domestic fundamentals; and by abolishing it to join the euro she has paid a cost in the form of a sub-optimal monetary policy. Spain's experience suggests a cautious approach with regards to the timing of further EMU enlargement.
Keywords: C51; C52; E43; E58; F37; 330; Spain; ECB; monetary policy; domestic fundamentals; compatibility; Geldpolitik; Zins; Öffentliche Anleihe; Internationaler Wettbewerb; Wirtschaftsreform; Währungsumstellung; Euro; Wirkungsanalyse; Spanien